Ethical role of students in corruption prevention in higher education - M.A. Suwandi; I.V. Brylina (Векторы благополучия: экономика и социум)
Universities are the place where the new generation of nations, future leaders of countries, is formed, educated and trained. Sociocultural changes associated with globalization, market competition, commodification of knowledge, and marketization of the university have penetrated into the academic environment, having a negative impact on the emergence of deviant practices in the field of education. Therefore, in recent years, close attention of various groups of researchers from different countries has been drawn to the study of transformations of university culture in general, in particular, the analysis of the reasons for the involvement of universities in corrupt practices and the identification of the potential for overcoming them. The theoretical methodology of the study, collection of library information, analysis, generalization, and reflection are used. It is argued that students, along with other agents of the university (teaching staff and university administration), can take on a significant role in preventing and eradicating corruption in the university environment, thanks to which a clean university environment free from acts of corruption can be created. The conclusion is made about the importance of the ethical role of students in corruption prevention in universities, since students are a significant agent of change and control, who, due to their characteristics, can act as role models of ethical anti‐corruption actions, monitor and report on corrupt actions, participate in student organizations, in public policy and use new information and communication technologies for anti‐corruption campaigns. Thus, students can play a socially significant role in creating a university environment free from corruption.